Effect of eight weeks vibration training on the lower limb basic ability and athletic performance of gymnasts - Mai Liu, H.-H.; Weng, S.-H.; Kao, Y.-H.; Huang, C.-F. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study explores the effects of 8 weeks vibration training on the basic ability (explosive power, speed, agility) and athletic performance (backward somersault) of the lower limbs of gymnasts. Sixteen gymnasts were randomly divided into vibration training group (VT) and control group (CON). Participants were trained for eight weeks and performed countermovement jump (CMJ), sprints, shuttle run, and backward somersault tests before the training, after 4 weeks, and 8 weeks of training. The significant level was set to a = .05. The results showed that the speed of VT increased significantly after 4 weeks of training, and the speed and agility of VT increased significantly after 8 weeks of training (p <.05). In conclusion, Gymnasts can improve their speed ability through 4 weeks of vibration training, and 8 weeks vibration training can improve their speed and agility.